2016
DOI: 10.1118/1.4966130
|View full text |Cite
|
Sign up to set email alerts
|

Development of a four‐axis moving phantom for patient‐specific QA of surrogate signal‐based tracking IMRT

Abstract: Purpose:The purposes of this study were two-fold: first, to develop a four-axis moving phantom for patient-specific quality assurance (QA) in surrogate signal-based dynamic tumor-tracking intensity-modulated radiotherapy (DTT-IMRT), and second, to evaluate the accuracy of the moving phantom and perform patient-specific dosimetric QA of the surrogate signal-based DTT-IMRT.Methods:The four-axis moving phantom comprised three orthogonal linear actuators for target motion and a fourth one for surrogate motion. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
2
20
1
Order By: Relevance
“…During treatment, a new data point is added to the training dataset every minute on average, with deletion of an older data point. 6,17,18 Poels et al 23 compared the accuracy of the correlation models derived for the CyberKnife and the Vero4DRT, and found no significant differences between the predictive accuracies when training was performed using high sampling intervals. In addition, the same authors in a different study developed an update method similar to that employed in the CyberKnife.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During treatment, a new data point is added to the training dataset every minute on average, with deletion of an older data point. 6,17,18 Poels et al 23 compared the accuracy of the correlation models derived for the CyberKnife and the Vero4DRT, and found no significant differences between the predictive accuracies when training was performed using high sampling intervals. In addition, the same authors in a different study developed an update method similar to that employed in the CyberKnife.…”
Section: Discussionmentioning
confidence: 99%
“…17 Next, a 4D model was constructed using the training data of target positions acquired over 20 s, employing sampling intervals of 80 or 320 ms. Each target position was calculated by reference to the centroid of fiducials embedded in a homogeneous cube placed on the moving phantom. The peak-to-peak amplitude of the detected target motions, and mean and standard deviation (SD) of the residual training error, were automatically calculated during the training process.…”
Section: C Accuracy Verification Of the 4d Models Trained With Thementioning
confidence: 99%
“…However, the accumulated dose from summation of all beams was within the tolerance. Mukumoto et al also reported that the peripheral dose to the planning target volume (PTV) was reduced under moving conditions [10].…”
Section: Point Dose Verificationmentioning
confidence: 99%
“…However, simultaneous delivery of IMRT and DTT is expected to increase the burden on the multi-leaf collimator (MLC) and the gimbal mechanism, causing an interplay effect. Mukumoto et al [10] verified the dose distribution during DTT IMRT using GAFCHROMIC EBT3 films (Ashland, Kentucky, USA). Depuydt, T. et al and Garibaldi, C. et al reported on log file analysis for DTT IMRT [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…16 A four-axis moving phantom for patient specific QA, in which four high precision prismatic actuators are used to control the center-of-gravity of the phantom, was also proposed recently. 17 The proposed moving phantom provides sufficiently high accuracy but can be costly. Use of an industrial robotic manipulator for a dosimetric phantom has also been attempted, 18 and evaluation of its positioning accuracy was performed using the log of the joint actuators of the manipulator.…”
mentioning
confidence: 99%